1995
DOI: 10.1074/jbc.270.35.20473
|View full text |Cite
|
Sign up to set email alerts
|

The Elongation Factor 3 Unique in Higher Fungi and Essential for Protein Biosynthesis Is an E Site Factor

Abstract: Two elongation factors drive the ribosomal elongation cycle; elongation factor 1 alpha (EF-1 alpha) mediates the binding of an aminoacyl-tRNA to the ribosomal A site, whereas elongation factor 2 (EF-2) catalyzes the translocation reaction. Ribosomes from yeast and other higher fungi require a third elongation factor (EF-3) which is essential for the elongation process, but the step affected by EF-3 has not yet been identified. Here we demonstrate that the first and the third tRNA binding site (A and E sites, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
132
1
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(149 citation statements)
references
References 34 publications
13
132
1
3
Order By: Relevance
“…5) showed weaker binding. As suggested before, this indicates that eEF3 binds to post-state ribosomes, and that ATP hydrolysis is required for eEF3 dissociation from the ribosome 4 .…”
Section: Saxs Analysis Of Eef3mentioning
confidence: 93%
See 2 more Smart Citations
“…5) showed weaker binding. As suggested before, this indicates that eEF3 binds to post-state ribosomes, and that ATP hydrolysis is required for eEF3 dissociation from the ribosome 4 .…”
Section: Saxs Analysis Of Eef3mentioning
confidence: 93%
“…It interacts with both ribosomal subunits [1][2][3] , competes with eEF2 for binding to ribosomes, and stimulates eEF1A-dependent binding of cognate aminoacyltRNA to the ribosomal A-site 1,4 . Because, according to the allosteric three-site model of the ribosomal elongation cycle, E-site release is required for efficient A-site binding, it has been suggested that eEF3 functions as a so-called 'E-site factor' 4,5 . Moreover, ATP hydrolysis by eEF3 is required in every elongation cycle to allow chasing of deacyltRNA from the E-site 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…70 eEF3 binds near the E-site and is necessary for clearance of the deacylated tRNA from the ribosome. 70,71 Cryo-EM analysis of the eEF3-80S complex (at 9.9A ) showed that the factor binds near the head of the 40S ribosomal subunit and makes contacts with both the 40S and 60S subunits. 71 The so-called HEAT domain of eEF3 was mapped to interact with eukaryote-specific extensions of uS13 and 2 protein-rich regions (unassigned due to low resolution) termed rpSX1 and rpSX2.…”
Section: Interaction Of 40s Ribosomal Proteins With Eef3mentioning
confidence: 99%
“…The in vitro-synthesized tRNA f Met showed clear mRNAdependent P site binding, comparing well with the in vivogenerated tRNA (data not shown). Templates for the MFmRNA were generated by linearizing plasmid pTZ-MF [kindly provided by K. Nierhaus, (17)] with SspI.…”
Section: Generation Of Phosphorothioate-containing Trnas Andmentioning
confidence: 99%